Complications of the nasal dorsum reconstruction using autologous or alloplastic grafts: evidence from systematic review and meta-analysis - Hudise,Jibril Y. (2022)
Abstract Introduction Augmentation rhinoplasty depends mainly on intact stable bony and cartilaginous parts. Many trials have used different materials as a graft to perform the operation and support the nose. Debate exists whether alloplastic or autogenic grafts are more appropriate. Common available alloplastic grafts include silicone, medpor, and gore-tex. Autogenic grafts are usually derived from costal cartilages. Warping, infection, and hypertrophic scars are the main complications of the procedure. Yet no subgroup analysis has been performed to investigate the effect of different risk factors. Objective To investigate the effect of different types of grafts and the association of the income level of the country on surgery complications. Methods A comprehensive literature search of articles was conducted in PubMed, Cochrane Library, Web of Science, and SCOPUS databases through October 2019. We included articles that used autologous or alloplastic grafts in nasal dorsum reconstruction surgery. We performed subgroup analysis according to the type of graft used, region, and income level of the country. A meta-regression analysis model was carried out from the period of 1999-2018, to study the incidence of these complications over time. Results The overall complication rate was 7.1%, which was higher in the alloplastic group (7.8%) than the autogenic group (6.9%). The most common complications were secondary surgery for re-correction (4.1%), infection (2.1%), warping (1.6%), and hypertrophic scars (1.6%). All outcomes were homogeneous (I2 < 50%). Conclusion Patients with autogenic grafts are less liable to develop complications than their peers reconstructed with alloplastic grafts. Moreover, Asian patients are less susceptible to overall rhinoplasty complications. Attention should be noted for low-income countries in which surgical complications are more prone to occur.